2004
DOI: 10.1073/pnas.0406173102
|View full text |Cite
|
Sign up to set email alerts
|

Baxdeletion prevents neuronal loss but not neurological symptoms in a transgenic model of inherited prion disease

Abstract: Transgenic Tg(PG14) mice express a mutant prion protein containing 14 octapeptide repeats, whose human homologue is associated with an inherited prion dementia. These mice develop a progressive neurological disorder characterized by ataxia and cerebellar atrophy, with massive apoptotic degeneration of granule neurons. Bax, a proapoptotic gene of the Bcl-2 family, plays a key role in regulating cell death in the nervous system. To analyze the role of Bax in the Tg(PG14) phenotype, we crossed Tg(PG14) mice with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
91
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 36 publications
9
91
0
Order By: Relevance
“…Misfolded monomers or oligomeric intermediates appear to be the more probable toxic species. This is consistent with recent data indicating that smaller subfibrillar particles with a mass equivalent to [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] PrP molecules are the most infectious moiety and may be much more toxic than larger amyloid fibrils or plaques [113].…”
Section: Prp In Aggresomessupporting
confidence: 80%
“…Misfolded monomers or oligomeric intermediates appear to be the more probable toxic species. This is consistent with recent data indicating that smaller subfibrillar particles with a mass equivalent to [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] PrP molecules are the most infectious moiety and may be much more toxic than larger amyloid fibrils or plaques [113].…”
Section: Prp In Aggresomessupporting
confidence: 80%
“…In addition, the study of the cytosolic form of PrP c have provided new insights regarding which signaling pathways could be presumably involved in prion disorders; for example, in aged transgenic mice overexpressing PrP c , mitochondrial localization of PrP c promotes neuronal apoptosis (Hachiya et al, 2005) and cytosolic PrP c failed to rescue Bax-induced cell death in yeast (Li and Harris, 2005), supporting the toxic properties of cytosolic PrP c in neurons (Rambold et al, 2006). However, it is necessary to take into account which of these related pathways are directly implicated in the "real" human or animal prion disease (Chiesa et al, 2005). In the other hand, prion pathology triggers primarily dysfunction and activation of glial cells rather than neuronal death, in contrast with other degenerative disorders (Prusiner, 1991;Prusiner, 1998a).…”
Section: Prp C Expression and Prion Pathologymentioning
confidence: 99%
“…Bcl-2 overexpression and BAX suppression have been extensively used to prevent cell death in several pathologic situations; for example, Bcl-2 overexpression in vivo largely delays clinical onset in a Familial Amyotrophic Lateral Sclerosis model (Kostic et al, 1997), and BAX suppression prevents neuronal depletion in a prion disease model (Chiesa et al, 2005). Consequently, four studies have recently reported that cell death in N-terminal truncated overpressing mice and in the Nagasaki line is regulated in a Bcl-2/BAX manner (Heitz et al, 2008;Heitz et al, 2007;Li et al, 2007a;Nicolas et al, 2007) (see Table 1).…”
Section: Bcl-2/bax and Prp C -Truncated Mouse Modelsmentioning
confidence: 99%
“…10 The dissociation between cell loss and synaptic loss is reinforced in prion models by studies showing that preventing neuronal degeneration does not prevent disease progression. 11,12 Studies on the slow Wallerian degeneration mutant mouse (Wld s ) demonstrated for the first time that degeneration of the synapse and axon are active autodestruc-tive processes, akin to programmed cell death, but differently regulated from death of the cell soma. 13,14 The loss of supernumerary synapses from the developing brain is well established and this may also involve tagging of the synapse by components of the complement cascade C1q and C3 for removal by microglia: it was suggested that a similar process might operate in glaucoma and by extension in other chronic neurodegenerative diseases.…”
mentioning
confidence: 99%